2016
DOI: 10.3389/fpls.2016.01364
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Wheat/Faba Bean Mixed Cropping or Rotation Systems on Soil Microbial Functionalities

Abstract: Cropping systems based on carefully designed species mixtures reveal many potential advantages in terms of enhancing crop productivity, reducing pest and diseases, and enhancing ecological services. Associating cereals and legume production either through intercropping or rotations might be a relevant strategy of producing both type of culture, while benefiting from combined nitrogen fixed by the legume through its symbiotic association with nitrogen-fixing bacteria, and from a better use of P and water throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 65 publications
3
36
0
1
Order By: Relevance
“…Faba bean exhibited the most significant N balance (N fixed -N offtake) (19.8 kg of N per tonne of grain production) among grain legumes cultivated in the EU (Baddeley et al, 2013). The integration of faba bean into cropping systems has revealed many potential advantages in terms of increasing yield and quality, reducing diseases and pests, and influencing soil microbial activity and functions (Köpke and Nemecek, 2010;Li et al, 2013;Wahbi et al, 2016). It was shown that the introduction of faba bean into crop rotation increases microbial populations (bacteria and fungi) and enzyme activities (dehydrogenase, phosphatase, arylsulfatase, β-glucosidase and arylamidase), and also increases the rate of carbon mineralization, as well as modifying microbial populations and the catabolic capability of soil microorganisms (Aschi et al, 2017;Lupwayi and Kennedy, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Faba bean exhibited the most significant N balance (N fixed -N offtake) (19.8 kg of N per tonne of grain production) among grain legumes cultivated in the EU (Baddeley et al, 2013). The integration of faba bean into cropping systems has revealed many potential advantages in terms of increasing yield and quality, reducing diseases and pests, and influencing soil microbial activity and functions (Köpke and Nemecek, 2010;Li et al, 2013;Wahbi et al, 2016). It was shown that the introduction of faba bean into crop rotation increases microbial populations (bacteria and fungi) and enzyme activities (dehydrogenase, phosphatase, arylsulfatase, β-glucosidase and arylamidase), and also increases the rate of carbon mineralization, as well as modifying microbial populations and the catabolic capability of soil microorganisms (Aschi et al, 2017;Lupwayi and Kennedy, 2007).…”
mentioning
confidence: 99%
“…It was shown that the introduction of faba bean into crop rotation increases microbial populations (bacteria and fungi) and enzyme activities (dehydrogenase, phosphatase, arylsulfatase, β-glucosidase and arylamidase), and also increases the rate of carbon mineralization, as well as modifying microbial populations and the catabolic capability of soil microorganisms (Aschi et al, 2017;Lupwayi and Kennedy, 2007). Moreover, the use of faba bean in crop rotation positively affected mycorrhizal colonization, which improves plant nutrient and water uptake, and enhances drought tolerance (Wahbi et al, 2016). The beneficial effects of legume influence on soil microbial activity could be connected with the biochemical composition and quantity of crop residues, including the higher amounts of organic carbon and nitrogen content incorporated into the soil through legume residues, as compared with crop rotation without legumes.…”
mentioning
confidence: 99%
“…Cropping system based on carefully designed species mixtures reveal many potential advantages interims of enhancing crop productivity, reducing pest and disease, and enhancing ecological service. Associating cereals and legume production through cropping system might be a relevant strategy of producing both types of crops while benefiting from combining nitrogen fixed by the legume through symbiotic association with nitrogen fixing bacteria and from better use of phosphorous and water through michrohezial association [30]. World population increases rapidly and global food production must be adapted to the requirements of human consumption.…”
Section: Role Of Pulse Crop Intercropping With Wheatmentioning
confidence: 99%
“…Intercropping wheat with faba bean is beneficial for increasing land productivity and soil health in many areas (Chapagain and Riseman, 2014;Wahbi et al, 2016b). However, theories that include temporal niche differentiation (Yu et al, 2015) and competition and recovery (Li et al, 2001) cannot fully explain wheat and faba bean performances in intercropping because they are roughly simultaneously sown and harvested at a similar plant height.…”
Section: Wheat Growth Is Stimulated By Interspecific Competition Aftementioning
confidence: 99%